Worsening vision at age 4–5 in England post‐COVID: Evidence from a large database of vision screening data. (3rd March 2023) - Shah, Rakhee; Edgar, David F.; Evans, Bruce J. W.
Abstract: Purpose: Myopia prevalence has increased in the UK at age 10‐16y, but little is known about younger children. We hypothesise that if the 'myopia epidemic' is affecting young children, then there will be increasing rates of bilateral reduced unaided vision (V) at vision screenings of children 4–5 years of age. Methods: Retrospective anonymised data from computerised vision screening at age 4–5 years were analysed from serial cross‐sectional data. Refractive error is not assessed in UK vision screening, so vision was investigated. Data were only included from schools that screened every year from 2015/16 to 2021/22. The criterion used was unaided monocular logMAR (automated letter‐by‐letter scoring) vision >0.20 in both the right and left eyes, so as to maximise the chances of detecting bilateral, moderate myopia rather than amblyopia. Results: Anonymised raw data were obtained for 359, 634 screening episodes from 2075 schools. Once schools were excluded where data were not available for every year and data were cleaned, the final database comprised 110, 076 episodes. The proportion (percentage and 95% CI) failing the criterion from 2015/16 to 2021/22 were 7.6 (7.2–8.0), 8.5 (8.1–8.9), 7.5 (7.1–7.9), 7.8 (7.4–8.2), 8.7 (8.1–9.2), 8.5 (7.9–9.0) and 9.3 (8.8–9.7), respectively. The slope of the regression line showed a trend for increasing rates of reduced bilateral unaided vision, consistent with increasing frequency of myopia ( p  = 0.06). A decreasing linear trendline was noted for children 'Under Professional Care'. Conclusions: For children 4–5 years of age, there were signs of reduced vision over the last 7 years in England. Consideration of the most likely causes support the hypothesis of increasing myopia. The increase in screening failures highlights the importance of eye care in this young population.